Could EU foresee and prevent the humanitarian crisis in Greece? The adopted strategies, results and future expectations for the Greek case. - Χοτρούδη, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2016)
Greek economy hit by the global financial crisis in 2007 fell into deep recession and has yet to recover. Continual deficits and accumulated public debt in 2009 drew a completely disappointing picture for Greek economy. Greece was the first European member to apply for financial assistance to its European partners that were caught unprepared. EU and IMF cooperated for the first time in history to solve financial turmoil that entered European region attacking members’ economy. The fear of a possible contagion was spread rapidly and there was an emergency for supporting institutions. We argue that IMF applied a traditional program without taking into consideration the heterogeneity and structural differences of European members separately so as to adjust the program. That resulted to an unsuccessful process for Greece, with a potential risk for a humanitarian crisis to start. IMF and EU did not pay the needed attention to the Greek weaknesses and did not provide an alternative or a revised theory when Greece run a second round of deep recession. Nevertheless there is still time for reconstructing effectively the economy, limiting the recession and opening the path to real recovery.
Θα μπορούσε η Ευρωπαϊκή Ένωση να προβλέψει και να αποτρέψει την ανθρωπιστική κρίση στην Ελλάδα; Οι υιοθετημένες στρατηγικές, αποτελέσματα και μελλοντικές προσδοκίες για την ελληνική περίπτωση.
Keywords: Οικονομική κρίση--Ελλάδα; Διεθνές Νομισματικό Ταμείο; Ελλάδα--Οικονομική πολιτική; Ελλάδα--Κοινωνικές συνθήκες; Ελλάδα--Οικονομικές συνθήκες; Οικονομία; Ύφεση; Ευρωπαϊκή Ένωση; Διεθνές Νομισματικό Ταμείο; Ανθρωπιστική κρίση